Does experience with digital storytelling help students to critically evaluate educational videos about history?. Issue 1 (1st April 2020) - Barsch, Sebastian
Educational videos are becoming increasingly important for schools. More and more often, students consume videos on YouTube in order to carry out school tasks. At the same time, the digital world is increasingly influencing perceptions of history. The internet contains numerous examples of how history is instrumentalized. Counterfeiting and manipulation distort historical information and abuse it for political purposes. This article presents the results of a research project on history teaching in a seventh grade (age 12–14) class in Germany. The study's aim was to find out if creating one's own videos using the method of digital storytelling generally leads to a more critical evaluation of educational videos. Students produced short videos on the subject of 'European expansion in the early modern period'. One group was secretly commissioned to portray the Europeans as superior to the indigenous societies of America, thus creating a manipulative video. At the end of the lesson, the students rated the credibility of the videos. In addition, interviews with students were conducted. The aim was to investigate whether students trained in digital storytelling could easily identify biased information. The data were analysed using qualitative text analysis. Findings show that students primarily judge videos based on aesthetic features, rarely adopting a media-critical perspective.